The revenue autonomy of self-governments in selected EU countries - Babczuk, Arkadiusz; Więznowski, Artur (Uniwersytet Ekonomiczny we Wrocławiu, 2008)
The subject of this article is the analysis of self-governments’ revenue autonomy in Poland and other selected EU countries. As an indicator we have chosen a share of own revenue in the structure of the whole self-governments’ revenue. For our research we would like to chose such countries which are comparable to Poland as regards their population, area and GDP. As the result, Spain, The Netherlands, Belgium, The Czech Republic, Hungary, Greece and Portugal have been chosen. Research reveals diversity of self-governments’ revenue autonomy level in these countries. A particularly high level of revenue autonomy is found in Spain, where over half of self-governments’ revenue is own revenue. In the case of some countries (Belgium, The Czech Republic, Hungary and Portugal) the share of own revenue in the structure of whole self-governments’ revenue exceeds 30%, but is lower than 50%. The lowest level of self-governments’ revenue autonomy is in The Netherlands and Greece. The Polish solution is compliant with the decentralized fiscal authority models as well as with centralized fiscal authority models
Argumenta Oeconomica, 2008, No 1 (20), s. 67-82
Keywords: local and regional self-governments; self-governments’ revenue autonomy; justice in spatial aspect; fiscal federalism